Management earnings forecasts and analyst forecasts: Evidence from mandatory disclosure system - Yutao Wang; Yunsen Chen; Juxian Wang (China Journal of Accounting Research, 2015)
Distinct from the literature on the effects that management earnings forecasts (MEFs) properties, such as point, range and qualitative estimations, have on analyst forecasts, this study explores the effects of selective disclosure of MEFs. Under China's mandatory disclosure system, this study proposes that managers issue frequent forecasts to take advantage of opportune changes in predicted earnings. The argument herein is that this selective disclosure of MEFs increases information asymmetry and uncertainty, negatively influencing analyst earnings forecasts. Empirical evidence shows that firms that issue more frequent forecasts and make significant changes in MEFs are less likely to attract an analyst following, which can lead to less accurate analyst forecasts. The results imply that the selective disclosure of MEFs damages information transmission and market efficiency, which can enlighten regulators seeking to further enhance disclosure policies.
Keywords: G14; G20; M41; 650; Management earnings forecasts; Selective disclosure; Analyst forecasts